THE DIMENSION OF TAWḤĪD IN THE DEVELOPMENT OF ISLAMIC LAW INSTITUTION: Quranic Exegesis Perspective - HAM, Musahadi (Al-Ahkam, 2017)
Tawḥīd is an essential vocabulary for Muslims. As the essence of belief in Allah, tawḥīd (monotheism) must be manifested in various aspects of Muslims life including the development of Islamic law institutions. The values of tawḥīd are regarded as the guarantors that the institution can represent the exact pattern for human relations in terms of being servants of God and of being fellow humans. That is why Muslims need to mobilize all intellectual potential in order to build legal institutions having benefits contextually and ethically without ignoring the faith. This paper tries to reconstruct how tawḥīd will be mobilized to fulfill these law expectations based on Qur’an.[]Tawḥīd adalah kosa kata penting bagi umat Islam. Sebagai esensi kepercayaan kepada Allah, tawḥīd (monoteisme) harus diwujudkan dalam berbagai aspek kehidupan umat Islam termasuk pengembangan institusi hukum Islam. Nilai tawḥīd dianggap sebagai penjamin bahwa institusi tersebut dapat mewakili pola pasti hubungan manusia dalam hal menjadi pelayan Tuhan dan sesama manusia. Itulah sebabnya umat Islam perlu memobilisasi semua potensi intelektual agar membangun institusi hukum yang memiliki manfaat secara kontekstual dan etis tanpa mengabaikan keimanan. Tulisan ini mencoba untuk merekonstruksi bagaimana tawḥīd dimobilisasi untuk memenuhi harapan-harapan hukum berdasarkan Qur’an.